Breeding potential of cassava (Manihot esculenta Crantz) in Mozambique - Da Silva, Anabela Matangue Zacarias (University of the Free State, 2008)
This study represents the first comprehensive genetic study based on local cultivars of Mozambique. Five cassava (Manihot esculenta Crantz) parents were crossed in a full diallel. The parents and F1 progeny were evaluated for eight agronomical and 17 morphological traits in two consecutive seasons. General combining ability (GCA) was higher than specific combining ability (SCA) for number of roots, root taste, fresh root yield, root pulp hardness and harvest index. Positive heterosis was seen for number of roots, fresh root weight and harvest index. Negative heterosis was present for cassava brown streak virus disease. Harvest index showed high broad sense heritability, which indicated that phenotypic variance was additive. The predictability ratio was close to unity, which confirmed that this trait is highly heritable, and determined by additive gene action. Cassava brown streak root necrosis had SCA effects significantly higher than GCA effects indicating the presence of non-additive genetic effects. A selection index comprised of the most relevant characters was compiled. Amplified fragment length polymorphism (AFLP) analysis showed high genetic similarity among 17 accessions. A total of 425 fragments were produced by eight primer combinations. Mocuba and Nikwaha were the most distinct among the accession and two heterotic groups were suggested. Morphological analysis showed genetic distance ranging from 0.105 to 0.833. The correlation coefficient between AFLP and agronomic clustering was not significant. The AFLP and morphological analysis did not group the accessions according to geographical origin. The principal component analysis provided diversity structure, suggesting the effectiveness of this analysis in genetic diversity studies. The narrow genetic similarity observed, indicates the need to introduce new cassava germplasm.

Hierdie studie verteenwoordig die eerste omvattende genetiese studie gebasseer op plaaslike cultivars van Mosambiek. Vyf cassava (Manihot esculenta Crantz) ouers is in ‘n volle dialleel gekruis. Die ouers en F1 nageslag is geëvalueer vir agt agronomiese en 17 morfologiese eienskappe in twee opvolgende seisoene. Algemene kombineervermoë was hoër as spesifieke kombineervermoë vir aantal wortels, wortel smaak, vars wortel opbrengs, wortel pulp hardheid en oesindeks. Positiewe heterose vir aantal wortels, vars wortel gewig en oesindeks is gevind. Negatiewe heterose is gesien vir cassava bruinstreepvirussiekte. Oesindeks het hoë breë sin oorerflikheid getoon, wat gewys het dat fenotipiese variansie additief is. Die voorspellingsverhouding was na aan een, wat bevestig dat hierdie eienskap hoogs oorerflik is en deur additiewe geenaksie bepaal word. Cassava bruinstreepvirussiekte het betekenisvol hoër spesifieke as algemene kombineervermoë getoon wat die teenwoordigheid van nie-additiewe effekte aangedui het. ‘n Seleksie indeks wat bestaan het uit die belangrikste eienskappe, is saamgestel. “Amplified fragment length polymorphism” (AFLP) analise het hoë genetiese ooreenkoms tussen die 17 genotipes aangetoon. ‘n Totaal van 425 fragmente is met agt priemstuk kombinasies geamplifiseer. Mocuba en Nikwaha was die mees uniek van die genotipes en twee heterotiese groepe is aangedui. Morfologiese analise het ‘n genetiese afstand tussen 0.105 en 0.833 aangetoon. Die korrelasie koeffisiënt tussen AFLP en agronomiese groepering was nie betekenisvol nie. Die AFLP en morfologiese analise het die inskrywings nie volgens geografiese areas gegroepeer nie. Die hoof komponent analise het ‘n diversiteitsstruktuur verskaf, wat die doeltreffendheid van hierdie metode vir genetiese diversiteitsstudies aantoon. Die nou sin oorerflikeidswaardes van die studie het die nodigheid uitgewys om nuwe cassava kiemplasma by die teelprogram in te sluit.
Thesis (Ph.D. (Plant Sciences: Plant Breeding))--University of the Free State, 2008
Keywords: Cassava -- Breeding -- Mozambique; Cassava -- Identification -- Mozambique; Mozambique; Selection index; AFLP; Morphology; Heritability; Heterosis; Combining ability